2022
DOI: 10.1002/tox.23592
|View full text |Cite
|
Sign up to set email alerts
|

EHD1 promotes the cancer stem cell (CSC)‐like traits of glioma cells via interacting with CD44 and suppressing CD44 degradation

Abstract: Plenty of evidence has shown that endocytosis plays a key role in cancer progression; however, its effects in the progression of cancer stem cells (CSCs) are still fragmentary. In the present study, we firstly identified that mammalian Eps15 homology domain protein 1 (EHD1), an endocytic and metastasis‐associated gene, was upregulated in the 3D non‐adherent spheres derived from glioma cells compared to that in the corresponding parental cells. Further functional experiments revealed that EHD1 knockdown reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…These cell biological findings raise the possibility that overexpression of EHD1 in tumors could promote RTK-dependent oncogenic signaling by enabling the cell surface display of RTKs on tumor cells. This idea is consistent with recent findings in which EHD1 overexpression has been observed in various cancers, often correlating with shorter survival, and cell-based studies using gene knockdown or overexpression strategies that support the role of EHD1 overexpression to promote tumorigenesis, chemotherapy resistance, epithelial-mesenchymal transition, stem cell behavior and glycolysis in various tumor models 615 . These studies have linked EHD1 overexpression to distal signaling alterations such as the activation of NFκB, β-catenin/c-Myc pathways that are not immediately linked to EHD1’s core vesicular traffic roles in endocytic recycling and Golgi to cell surface RTK traffic.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…These cell biological findings raise the possibility that overexpression of EHD1 in tumors could promote RTK-dependent oncogenic signaling by enabling the cell surface display of RTKs on tumor cells. This idea is consistent with recent findings in which EHD1 overexpression has been observed in various cancers, often correlating with shorter survival, and cell-based studies using gene knockdown or overexpression strategies that support the role of EHD1 overexpression to promote tumorigenesis, chemotherapy resistance, epithelial-mesenchymal transition, stem cell behavior and glycolysis in various tumor models 615 . These studies have linked EHD1 overexpression to distal signaling alterations such as the activation of NFκB, β-catenin/c-Myc pathways that are not immediately linked to EHD1’s core vesicular traffic roles in endocytic recycling and Golgi to cell surface RTK traffic.…”
Section: Introductionsupporting
confidence: 91%
“…While our studies focus on the linkage of EHD1 with an RTK, EHD1 overexpression may also regulate other oncogenesis-related cell surface receptors, given its broader roles. Indeed, EHD1 overexpression was shown to promote cancer stem cell-like traits in glioblastoma and lung cancer by promoting CD44 recycling while suppressing its degradation 60, 61 , promote cisplatin resistance in NSCLC by regulating cisplatin accumulation in cells, presumably by regulating transporter levels 62 , and potentiate angiogenesis by promoting b2 adrenergic receptor recycling 63 . Cell biological studies have also shown a positive role of EHD1 in β1 integrin recycling 45 .…”
Section: Discussionmentioning
confidence: 99%
“…These cell biological findings raise the possibility that overexpression of EHD1 in tumors could promote RTK-dependent oncogenic signaling by enabling the cell surface display of RTKs on tumor cells. This idea is consistent with recent findings of EHD1 overexpression in various cancers, often correlating with shorter survival, and the cell-based studies using gene knockdown or overexpression strategies that support the role of EHD1 overexpression to promote tumorigenesis, chemotherapy resistance, epithelial-mesenchymal transition, stem cell behavior, and glycolysis in various tumor models [6][7][8][9][10][11][12][13][14][15] . These studies have linked EHD1 overexpression to distal signaling alterations such as the activation of NFkB, β-catenin, and c-Myc pathways that are not immediately linked to EHD1's core vesicular traffic roles in endocytic recycling and Golgi to cell surface RTK traffic.…”
supporting
confidence: 91%
“…Our studies demonstrating a requirement of EHD1 for IGF-1R cell surface traffic and signaling as a key component for its requirement for tumorigenic and metastatic behaviors of EWS cell models raise the question of whether EHD1 might be a suitable target in EWS since the impact of IGF-1R targeting has been low to modest 31,34,37,44 . Given the EHD1 regulation of IGF-1R and other RTKs 4,5 as well as its targeting of additional pathways shown in other cancers 9,11,12,[14][15][16]70 , it appears likely that EHD1 targeting may still be viable and may potentially be combined with IGF-1R targeting. Additionally, the cell surface levels of RTKs not only dictate the levels of ligand-induced and kinase-dependent signaling as documented for IGF-1R in this study, but also dictate their kinase-independent signaling as demonstrated for several RTKs including EGFR and IGF-1R [71][72][73][74][75][76] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation